Literacy and learning - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Advances in learning and behavioral disabilities ;, 2010)
Among the most commonly reported characteristics of individuals with learning and behavioral disabilities are significant and persistent problems with literacy acquisition. Fortunately, applied research has revealed a number of methods for facilitating literacy learning among individuals with learning and behavioral disabilities. Included in this volume are chapters from a group of internationally-prominent authors, addressing important issues in the conceptualizing, assessing, and treating problems in literacy. In addition, current research in writing for students with learning and behavioral disabilities is described. A final chapter address the implications of research with exceptional individuals for general understanding of learning and cognition. This volume is intended to be of interest to clinicians, teachers, researchers, graduate students, and many others interested in literacy and learning of individuals with learning and behavioral disabilities.